Changes in typological and spatial boundaries between neighbouring communities of Potentitlo albae-Quercetum and Tilio-Carpinetum - Anna Justyna Kwiatkowska; Barbara Solińska-Górnicka (Acta Societatis Botanicorum Poloniae, 2014)
The sample area of 2.8 ha, divided into 100 m2 square quadrats, comprised two, distinguishable by traditional methods, oak forest patches and a fragment of a neighbouring mixed oak-hornbeam forest. The classification of quadrats was conducted by association analysis. Their identification and interpretation were performed on the basis of the systematic value and fraction of species of the characteristic oak forest combination in each distinguished quadrat group, as well as the range of distinguished communities. It appeared that due to the hornbeam invasion into the oak forest habitat, species forming the characteristic oak forest combination receded and the community area decreased. The data enabled reconstruction of the phases of oak forest recession. They corresponded to the successive phases of the encroachment of hornbeam undergrowth in the analysed area.